Prevalence of multidrug-resistant bacteria colonisation among asylum seekers in western Switzerland. Issue 4 (July 2021) - Kenfak-Foguena, Alain; Nahimana Tessemo, Immaculée; Bertelli, Claire; Merz, Laurent; Cometta, Alain; Blanc, Dominique; Senn, Laurence; Petignat, Christiane
The recent increase of migration to Europe represents a risk of increased the prevalence of multidrug-resistant (MDR) bacteria. We conducted a cross-sectional study among asylum seekers admitted at two hospitals in Switzerland. Of the 59 patients included, 9 (14%) were colonised by a MDR bacteria, including 5 (8.5%) methicilin-resistant Staphylococcus aureus (MRSA) and 4 (6.8%) extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae . No patient carried both ESBL-producing bacteria and MRSA. None of the patients carried a vancomycin-resistant Enterococcus (VRE) or a carbapenem-resistant Enterobacteriaceae (CRE). Colonisation with MDR bacteria was not associated with hospitalisation abroad or recent arrival in Switzerland. Whole genome sequencing analysis allowed us to exclude transmission between patients. The prevalence of MDR bacteria carriage is moderate among asylum seekers in western Switzerland. Further surveillance studies are necessary to determine if there is a risk of dissemination of pathogens into the local population.